The secret - Byme rhma (New York : Pocket Books, 2006)
The saga of the feud between the Goode and Fier families begins during the witch hunts in Massachusetts in the late seventeenth century.
"An Archway paperback."
"RL 7+"--T.p. verso.
Keywords: Witchcraft -- Juvenile fiction; Horror tales